Occupational health in aviation: a cross-sectional study of barodontalgia among Malaysian air force pilots - Abidin, Sulhi; Mohd Nazri, Sofia Azreena; Mazlan, Nurhidayu; Mat Daud, Muhamad Sharifuddin; Haron, Mohammed Haizar; Abu Muslim, Munawarah Silam; Lin, Galvin Sim Siang (BMC, 2025)
Background Barodontalgia, or pressure-induced dental pain, poses a significant occupational risk to pilots, potentially impairing flight performance and safety. The present study aimed to determine the prevalence of barodontalgia among Malaysian military pilots, identify the associated risk factors, and examine its relationship with flight performance.